Reproduction: economics of reproductive efficiency - Albert De Vries (Revista Colombiana de Ciencias Pecuarias, 2017)
Greater pregnancy rates are always more profitable when they can be accomplished free. The gain in profit is decreasing with greater pregnancy rates. Therefore, less can be spend to further increase pregnancy rate. However, the published benefits of greater pregnancy rates (improved reproductive efficiency) are incomplete and are underestimated. The benefits from greater pregnancy rates depend on the strategy followed, such as use of sexed semen and of selling surplus heifers. Genomic testing of females on the farm can be profitable, depending on the fraction surplus heifers that can be created, and on smart breeding decisions regarding the use of sexed and beef semen. The value of these options increases with better reproductive efficiency.